Aberrant Mitochondrial Dynamics and Exacerbated Response to Neuroinflammation in a Novel Mouse Model of CMT2A - Filippos Stavropoulos (MDPI AG, 2021)
Charcot-Marie-Tooth disease type 2A (CMT2A) is the most common hereditary axonal neuropathy caused by mutations in MFN2 encoding Mitofusin-2, a multifunctional protein located in the outer mitochondrial membrane. In order to study the effects of a novel MFN2K357T mutation associated with early onset, autosomal dominant severe CMT2A, we generated a knock-in mouse model. While Mfn2K357T/K357T mouse pups were postnatally lethal, Mfn2+/K357T heterozygous mice were asymptomatic and had no histopathological changes in their sciatic nerves up to 10 months of age. However, immunofluorescence analysis of Mfn2+/K357T mice revealed aberrant mitochondrial clustering in the sciatic nerves from 6 months of age, in optic nerves from 8 months, and in lumbar spinal cord white matter at 10 months, along with microglia activation. Ultrastructural analyses confirmed dysmorphic mitochondrial aggregates in sciatic and optic nerves. After exposure of 6-month-old mice to lipopolysaccharide, Mfn2+/K357T mice displayed a higher immune response, a more severe motor impairment, and increased CNS inflammation, microglia activation, and macrophage infiltrates. Overall, ubiquitous Mfn2K357T expression renders the CNS and peripheral nerves of Mfn2+/K357T mice more susceptible to mitochondrial clustering, and augments their response to inflammation, modeling some cellular mechanisms that may be relevant for the development of neuropathy in patients with CMT2A.